Genetic contribution to variation in atherothrombotic phenotypes in the Asian Indian population - Rao, Veena S.; Khadrinarasimhaih, Natesha B.; Kanjilal, Saikat; Mukerjee, Manjari; Kakkar, Vijay V. (Thrombosis and Haemostasis, 2009)
Coronary artery disease (CAD) is a multifactorial disease, and family history is the best available tool to assess gene-environment interaction. This study addressed the heritability of quantitative traits, namely lipid, coagulation/fibrinolysis and pro-inflammatory markers in the ongoing family-based Indian Atherosclerosis Research Study and assessed the effect of the type/lineage of CAD family history on inheritance patterns in the highrisk Indian population. A total of 518 families comprising 2,305 individuals were recruited in phase I of the IARS; of these, 1,195 individuals from 220 families were included in the heritability analysis. With the exception of leptin, all phenotypes exhibited significant age- and sex-adjusted heritability (p<0.0001). Amongst all the phenotypes analysed after adjustment for confounding factors, the significantly higher heritability estimates of triglycerides (0.53, p<0.0001), lipoprotein (a) (0.83, p<0.0001) and interleukin-6 (0.46, p<0.0001) with low spouse pair correlations identifies them as possible CAD risk factors. Families with parental history of CAD had onset of CAD symptoms at much younger ages with significantly higher heritability of proinflammatory markers, whereas in families with sibling history of CAD, more risk factors were present at significantly higher levels. Triglycerides, lipoprotein (a) and interleukin-6 appear to be promising atherothrombotic candidate phenotypes in this population. Genes controlling these phenotypes are possible candidate genes linked with CAD. An informed understanding and incorporation of ‘family history’ as a screening tool may help in the prevention and pre-emption of CAD.
Keywords: Inflammation; SOLAR; atherosclerosis